2019
DOI: 10.1155/2019/4128682
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Microbiota in the Diabetic Peripheral Artery Disease

Abstract: Vascular complications of diabetes mellitus represent a major public health problem. Although many steps forward have been made to define the causes and to find the best possible therapies, the problem remains crucial. In recent years, more and more evidences have defined a link between microbiota and the initiation, promotion, and evolution of atherosclerotic disease, even in the diabetic scenario. There is an urgency to develop the knowledge of modern medicine about the link between gut microbiota and its ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 205 publications
(277 reference statements)
0
19
0
Order By: Relevance
“…In fact, TNF-α promotes the reduction of insulin receptor substrate 1 (IRS-1) mRNA and GLUT4mRNA, leading to insulin resistance and hyperglycemia [12] Moreover, Massaro and coworkers showed that peroxisome proliferator activated receptor (PPAR) alpha/gamma agonists attenuated insulin resistance in human adipocytes, reducing pro-inflammatory mediators including IL-6, CXC-L10 and monocyte chemoattractant protein (MCP-1), supporting the pathogenic role of inflammation in DM development [13]. Hyperglycemic environment is even characterized by enhanced production of reactive oxygen species (ROS), formation of advanced glycation end products (AGEs), activation of protein C kinase (PCK), and activation of polyol pathway [14]. All these factors promote a pro-inflammatory cytokines milieu, including TNF-α, IL-1β, IL-6-IL-8 and HMGB1, which contribute to endothelial damage, development of atherosclerosis and impaired angiogenesis, leading actors in diabetic vascular complications [15].…”
Section: Diabetes Mellitusmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, TNF-α promotes the reduction of insulin receptor substrate 1 (IRS-1) mRNA and GLUT4mRNA, leading to insulin resistance and hyperglycemia [12] Moreover, Massaro and coworkers showed that peroxisome proliferator activated receptor (PPAR) alpha/gamma agonists attenuated insulin resistance in human adipocytes, reducing pro-inflammatory mediators including IL-6, CXC-L10 and monocyte chemoattractant protein (MCP-1), supporting the pathogenic role of inflammation in DM development [13]. Hyperglycemic environment is even characterized by enhanced production of reactive oxygen species (ROS), formation of advanced glycation end products (AGEs), activation of protein C kinase (PCK), and activation of polyol pathway [14]. All these factors promote a pro-inflammatory cytokines milieu, including TNF-α, IL-1β, IL-6-IL-8 and HMGB1, which contribute to endothelial damage, development of atherosclerosis and impaired angiogenesis, leading actors in diabetic vascular complications [15].…”
Section: Diabetes Mellitusmentioning
confidence: 96%
“…Peripheral arterial disease (PAD), and in particular the lower extremities (LE) PAD is a form of atherosclerosis that affects the arteries of the lower limbs, leading to several complications such as critical limb ischemia, acute limb ischemia, tissue necrosis and gangrene [79,80]. It represents a major public health problem and, in 2010, 202 million people globally was affected by PAD [81], with a prevalence of 20-30% in patients with DM [82], the major risk factor for the disease [14]. Different mechanisms contribute to the development of PAD in a diabetic environment and inflammatory process has been widely recognized as the major player of atherosclerotic progression of lower limbs [57,79,83,84].…”
Section: Hmgb1 Diabetes Mellitus and Peripheral Arterial Diseasementioning
confidence: 99%
“…[116][117][118] To date, there are no established therapies to reduce these uremic toxins, except kidney replacement therapy. In this regard, gut microbiota may be an interesting potential therapeutic target, 119 as they produce these uremic toxins and could be manipulated through dietary modifications, medication, or fecal transplantation.…”
Section: Key Pathophysiology Of Pad In Ckd With Diagnostic and Therapeutic Implicationsmentioning
confidence: 99%
“…Therefore, the abundance of indole compounds in the gut is often evaluated as a biomarker in clinical specimens and has various applications in the pharmaceutical industry (Darkoh et al ., 2015 ). A targeted metabolomics study to identify the role of microbial metabolites in advanced atherosclerosis patients showed that the plasma levels of these metabolites (indole and phenyl derivatives) are correlated with postoperative outcomes, thereby suggesting that these compounds may serve as biomarkers in atherosclerosis (Table 3 ) (Cason et al ., 2018 ; Biscetti et al ., 2019 ).…”
Section: Indolic Metabolites As Biomarkers Of Diseasementioning
confidence: 99%
“…Qualitative (composition) or quantitative (population) changes in the gut microbiota can greatly influence the physiology of the host, contributing to several chronic diseases such as malnutrition, obesity, neurological disorders, cancers, inflammatory bowel disease (IBD), type 2 diabetes, atherosclerosis, metabolic syndromes, and liver diseases (Hendrikx & Schnabl, 2019 ). Disruption of symbiosis (dysbiosis) can occur due to multiple factors including diet, environmental factors, stress, aging, drug use, etc., which alter systemic levels of indoles (Biscetti et al ., 2019 ; Shi et al ., 2020 ). Although many microbes can synthesize tryptophan through the chorismate‐linked biosynthetic pathway, proteolytic activities are the major source of tryptophan for gut bacteria.…”
Section: Introductionmentioning
confidence: 99%